Definición conceptual de calidad y de excelencia en la educación superior en el contexto universitario chileno - Arriagada-Poblete, Carla; Gálvez-Gamboa, Francisco A.; Adasme-Jara, Benjamín (Universidad de Costa Rica, 2023)
The general objective of this study was to collectively construct the concepts of quality and excellence for a Chilean university as part of the updating of its quality policy, within the framework of the permanent search for continuous improvement within the institution. A theoretical review of both concepts was carried out, which allowed establishing that quality is a widely studied topic in higher education, but not the idea of excellence, which has been researched to a lesser extent. It was determined that a theoretical construction is not sufficient for their definitions, since both concepts have a multidimensionality and are dependent on the context to which they belong. Consequently, it was necessary to highlight the opinions of the different members of the university community in their definition. It was decided to apply a qualitative and exploratory approach based on the opinions of the different strata, where 75 people participated in a survey conducted through focus groups applied in August 2020 and October 2021. Subsequently, a content analysis was carried out, which established the following results: each definition of the concepts must be concrete and include an approach that considers the context and the elements of the university's work, such as objectives, identity, purposes, mission and institutional vision; the definition of the concept of excellence must explicitly include quality, so that the relationship between both definitions is visualized.